Age-related changes in consolidation of perceptual and muscle-based learning of motor skills - Spencer, Rebecca M.; PACE-SCHOTT, EDWARD F. (Frontiers in Aging Neuroscience, 2013)
Improvements in motor sequence learning come about via goal-based learning of the sequence of visual stimuli and muscle-based learning of the sequence of movement responses. In young adults, consolidation of goal-based learning is observed after intervals of sleep but not following wake, whereas consolidation of muscle-based learning is greater following intervals with wake compared to sleep. While the benefit of sleep on motor sequence learning has been shown to decline with age, how sleep contributes to consolidation of goal-based versus muscle-based learning in older adults has not been disentangled. We trained young (n=62) and older (n=50) adults on a motor sequence learning task and re-tested learning following 12 hr intervals containing overnight sleep or daytime wake. To probe consolidation of goal-based learning of the sequence, half of the participants were re-tested in a configuration in which the stimulus sequence was the same but, due to a shift in stimulus-response mapping, the movement response sequence differed. To probe consolidation of muscle-based learning, the remaining participants were tested in a configuration in which the stimulus sequence was novel, but now the sequence of movements used for responding was unchanged. In young adults, there was a significant condition (goal-based v. muscle-based learning) by interval (sleep v. wake) interaction, F(1,58)=6.58, p=.013: Goal-based learning tended to be greater following sleep compared to wake, t(29)=1.47, p=.072. Conversely, muscle-based learning was greater following wake than sleep, t(29)=2.11, p=.021. Unlike young adults, this interaction was not significant in older adults, F(1,46)=.04, p=.84, nor was there a main effect of interval, F(1,46)=1.14, p=.29. Thus, older adults do not preferentially consolidate sequence learning over wake or sleep.